KEPATUHAN PAJAK PROGRAM INSENTIF TAX AMNESTY: SEBUAH PENDEKATAN MIXED METHODS DAN BUKTI EMPIRIS PADA WAJIB PAJAK (WP) - Martdian Ratna Sari (Ultima Accounting : Jurnal Ilmu Akuntansi, 2019)
Various incentive programs in terms of potential have been completed, such as sunset policy program, e-spt program, e-filling, e-billing, Tax Payer Year (TPWP) and others. Ironically, the various programs have not been effectively able to increase acceptance and. Tax-Amnesty 2016, this study is intended to explore the tax amnesty phenomenon pursued by the Directorate General of Taxation in increasing the amount of state revenue and increasing compliance from the taxpayers. In fact, data on the realization of the receipt of pardons until October 2016 showed significant results and proved the WP OP enthusiastic enough to redeem the debt and reveal all income and possessions. Jackson and Miliron (1986) describe economic factors such as law / law / law. The criticism of this study on Jackson and Miliron, (1986) aimed at the concept of tax reporting complexity did not apply as a determinant of the success of Tax-Amnesty. Using a mixed method that focuses on a qualitative approach at the beginning of the research phase, this study uses the technique of the Most Significant Change (MSC) method to obtain the changes that form the basis of the preparation of thought and the making of indicators. Data analysis techniques using factor analysis are useful for feasibility purposes of each measurement indicator.